Austin’s mantle, or who’s (not) afraid of John L. Austin? On 50 years of speech act theory, and how Rajan saves J.L. Austin from himself and others - Mey, Jacob L. (2017)
The article places the person of Professor Kanavillil Rajagopalan within the context of his many years of research and teaching at various universities in Brazil. It is argued that his efforts to advocate a new approach to linguistics, based on the notion of ‘speech acts’, was not always well received by the practicing linguists of his day and age. Moreover, while researching the foundations of speech act theory from its inceptions, it became clear to Rajan that the doxa of ‘Searle merely codifying and cleaning up Austin’s somewhat unruly legacy’ does not hold. The common opinion represented by this view does injustice, both to Searle as an independent thinker and to Austin as an original philosopher in his own right, who not just speaks through a Searlean mouthpiece. In particular, people have not paid attention to an essential element of the Austinian oeuvre: his persistent distancing himself from all iron-clad and rigid theorizing; in addition, Austin’s humor played always a big role in his presentations, both orally and in writing. Rajan thus creates a more nuanced picture, both of the theory itself and of its two great protagonists, Austin and Searle.